Refractive and Visual Outcomes of Surgical Treatments for High Myopia - Robert Edward T. Ang, MD; Maria Rachelle Katrina C. Solis, MD; Maria Luisa Patricia C. Solis, MD; Emmerson M. Cruz, MD; Albert G. Dela Cruz, MD; Rosalie Mae M. Reyes, MD (Philippine Journal of Ophthalmology)
Objective: To present the refractive and visual outcomes of refractive surgical treatment options in high myopia.